The Changes in Rats with Sciatic Nerve Crush Injury Supplemented with Evening Primrose Oil: Behavioural, Morphologic, and Morphometric Analysis - Ramli, D.; Aziz, I.; Mohamad, M.; Abdulahi, D.; Sanusi, J. (Hindawi, 2017)
Nerve crush injuries are commonly used models for axonotmesis to examine peripheral nerve regeneration. As evening primrose oil (EPO) is rich in omega-6 essential fatty acid component and gamma-linolenic acid, studies have shown the potential role of EPO in myelination. Seventy-two healthy adult Sprague-Dawley rats were classified into three groups: normal group, control group, and experimental group. The result indicates that there was significant difference in toe-spreading reflex between the normal and the control groups (, ) and the normal and the EPO groups (, ) and significant difference between EPO and the control groups (, ). Regeneration of axons and myelin in nerve fibre in the EPO-treated group developed better and faster than in the control group. In the control group, the shape of the axon was irregular with a thinner myelin sheath. In the experimental group, the shape of the axons, the thickness of the myelin sheath, and the diameter of the axons were almost the same as in the normal group. In conclusion, EPO supplementation may be beneficial as a therapeutic option for disturbances of nerve interaction.